Pengaruh Tempat Tumbuh dan Lama Penyulingan secara Hidrodestilasi terhadap Rendemen dan Profil Kandungan Kimia Minyak Atsiri Daun Kemangi (Ocimum canum Sims L.) - Syamsu Nur; Junaedy Aryanto Baitanu; Sahibuddin A Gani (Jurnal Fitofarmaka Indonesia, 2019)
Kemangi (Ocimum canum Sims L.) is one of the plants producing essential oils. Kemangi essential oil is taken from the stem and leaves. This study aims to determine the precentage of the yield of kemangi leaf oil and to identify the content of the chemical compounds of essential oils found in kemangi leaves based on the comparison of the place of growth and duration of distillation. Kemangi leaf samples were obtained from the Bontoala sub-district and from Tinggimoncong sub-district of South Sulawesi. The extraction method of essential oils of kemangi leaves is done by the method of distilation/hydrodestilation using three variations of distillation time, namely 6 hours, 12 hours and 18 hours. Based on the results of the study, it can be concluded that the kemangi leaf essential oil which has the highest yield is from Tinggimoncong sub-district of South Sulawesi, which is 3.325 % with distilation time for 18 hours, GC-MS identification results also show that kemangi leaves essential oil from Tinggimoncong sub-district of South Sulawesi has 93 components of chemical compounds with 5 main components, namely: 5-heptene-2-one, 6-methyl, 1,6-octadien-3-ol, 3,7-dimethyl, α-Terpeniol, 2,6-octadienal, 3,7-dimethy (E), eugenoland also has a component of minor compounds, namely: citral, lynalil acetate, eucalyptol, geraniol, verbenol, carveol, and trans-isoeugenol.